Determine the effect of punch strokes on hearing levels of boxers - Pala, Ragip (Drunpp-Sarajevo, 2012)
Although the injury risks of boxing is well known, this sport continuous to attract athletes and an increase of introduction to boxing is observed in the last decade. In terms of injury locations, head and face are reported as most common sports. Present study aimed to examine the hearing differences of elite amateur boxers as a result of punch strokes in boxing. Subjects are interested in active boxing for 5-14 years (mean 6.67) and between the age of 18-32 (mean 21.71). Screened group consisted of 21 male boxers. Auditory brainstem responses, pure tone and high frequency audiogram tests were conducted for boxers and unscreened groups in the standard acoustically controlled rooms using Interacoustics Clinical Computer Audiometer. Mean +/- standard deviations are reported. Groups were compared by Student's t test p<0.05. Auditory brainstem responses and pure tone values were determined in range of I-V inter-pick latency (ms). There were no statistically significant differences in the hearing level of elite amateur boxers in contrast to non-boxers. It is seen to be important that amateur boxers wear protective materials as a helmet and mouth guard to minimize the risk of injury. The use of protective equipment must be encouraged for boxer's health.
Keywords: Hearing; boxer; punch; boxing; sport